2002
DOI: 10.1002/chem.200390034
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Syntheses of Fluorous Aryl Iodides and Hypervalent Iodine Compounds: ArI(L)n Reagents That Are Recoverable by Simple Liquid/Liquid Biphase Workups, and Applications in Oxidations of Hydroquinones

Abstract: Iodinations of the ortho, meta, and para fluorous arenes (R(f8)CH(2)CH(2)CH(2))(2)C(6)H(4) (R(f8)=(CF(2))(7)CF(3)) with I(2)/H(5)IO(6) in AcOH/H(2)SO(4)/H(2)O give 3,4-(R(f8)CH(2)CH(2)CH(2))(2)C(6)H(3)I (5) and the analogous 2,4- (6) and 2,5- (7) isomers, respectively. Spectroscopic yields are >90 %, but 5 and 7 must be separated by chromatography from by-products (yields isolated: 70 %, 97 %, 61 %). Reaction of 1,3,5-(R(f8)CH(2)CH(2)CH(2))(3)C(6)H(3) with PhI(OAc)(2)/I(2) gives 2,4,6-(R(f8)CH(2)CH(2)CH(2))(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 73 publications
0
48
0
1
Order By: Relevance
“…[11] IBA (1) and its derivatives are seldom used in synthesis owing to the decreased reactivity of these reagents as oxidants, especially as hypernucleofuges. [12] Inspired by the increased solubility and reactivity of [bis(trifluoroacetoxy)iodo]pentafluorobenzene [13] and other hypervalent iodine reagents with fluorous side chains, [14] we proposed that fluorination of the arene in the parent 2-iodobenzoic acid should solve many of the problems associated with cyclic iodanes. In this communication, we report what we believe to be the first hypervalent derivatives of 2,3,4,5-tetrafluoro-6-iodobenzoic acid (5) and discuss their structures and reactivities.…”
mentioning
confidence: 99%
“…[11] IBA (1) and its derivatives are seldom used in synthesis owing to the decreased reactivity of these reagents as oxidants, especially as hypernucleofuges. [12] Inspired by the increased solubility and reactivity of [bis(trifluoroacetoxy)iodo]pentafluorobenzene [13] and other hypervalent iodine reagents with fluorous side chains, [14] we proposed that fluorination of the arene in the parent 2-iodobenzoic acid should solve many of the problems associated with cyclic iodanes. In this communication, we report what we believe to be the first hypervalent derivatives of 2,3,4,5-tetrafluoro-6-iodobenzoic acid (5) and discuss their structures and reactivities.…”
mentioning
confidence: 99%
“…Results obtained in the present work are also intended to provide further guidelines for the rational design of fluorous-tagged stable nitroxyl radicals and for the development of all-fluorous catalytic systems. In this context, the combination of fluoroustagged TEMPO derivatives with a recyclable fluorous version of BAIB [48] and the use of molecular oxygen as the primary oxidant are worth investigating.…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Therefore, various types of recyclable hypervalent iodine reagents have been reported. First, the polymer-supported hypervalent iodine reagents, such as poly(diacetoxyiodo) styrene (PDAIS) and poly[bis(trifluoroacetoxyiodo)] styrene (PBTIS), incorporating phenyliodine(III) diacetate (PIDA) and phenyliodine(III) bis(trifluoroacetate) (PIFA) in their polymer backbones were developed.…”
Section: Resultsmentioning
confidence: 99%
“…First, the polymer-supported hypervalent iodine reagents, such as poly(diacetoxyiodo) styrene (PDAIS) and poly[bis(trifluoroacetoxyiodo)] styrene (PBTIS), incorporating phenyliodine(III) diacetate (PIDA) and phenyliodine(III) bis(trifluoroacetate) (PIFA) in their polymer backbones were developed. [41][42][43][44][45][46][47][48] Inspired by this study, other chemists have also reported new recyclable hypervalent iodine compounds having fluorous tags [49][50][51][52] and ionic supports. [53][54][55] We have previously developed a structurally new recyclable hypervalent iodine reagent 1a, namely, 1,3,5,7-tetrakis[4-(diacetoxyiodo) phenyl] adamantane ( Fig.…”
Section: Resultsmentioning
confidence: 99%